Influence of the Always-on Service of Little Traffic on Ev-Do Network and Optimization - Xiaoming He; Man Jia; Zhihua Liu (Dianxin kexue)
Influence of the always-on service of 1ittle traffic on Ev-Do network was analyzed. Optimization solutions especia11y for the always-on service of 1ittle traffic were given. Also，the coping strategies such as wireless operation index forecast and traffic guidance were put forward.